Queering Smart Decarceration: Centering the Experiences of LGBTQ+ Young People to Imagine a World Without Prisons - Hereth, Jane; Bouris, Alida (Affilia, 2020)
Addressing mass incarceration through smart decarceration initiatives is one of the Grand Challenges for Social Work named by the American Academy of Social Work Welfare and Research. The exponential growth of the U.S. prison system is largely due to legislation that targets marginalized communities, including people of color, poor people, people with mental illness, and those living with disabilities, as well as lesbian, gay, bisexual, transgender, and queer (LGBTQ+) people of all ages. In this article, we seek to complicate the current conversation on smart decarceration by arguing that social workers committed to addressing mass incarceration should engage abolitionist theory, politics, and organizing in their work in order to effectively address the root causes driving the buildup of the prison nation. We engage feminist and queer theories as two theoretical interventions that can guide this work. We next describe how LGBTQ+ youth enter the criminal legal system, highlighting how normative systems of gender and sexuality subject LGBTQ+ youth to punitive policing, surveillance, and discipline. Finally, we share three models of prison abolitionist organizing led by LGBTQ+ people of color as case studies. By examining how these organizations embrace queer and feminist abolitionist frameworks, we identify concrete ways that social workers can adopt abolitionist principles and practices in their work to address mass incarceration.